2019
DOI: 10.1088/1361-6595/ab279b
|View full text |Cite|
|
Sign up to set email alerts
|

Non-isothermal sheath model for low pressure plasmas

Abstract: The evolution of the electron mean energy in the pre-sheath and the sheath of a low pressure plasma bounded by two planes is investigated with 1D particle in cell simulations. We observed that the electron mean energy is not constant in the sheath, but instead decreases significantly from the bulk towards the wall. From the simulations, a polytropic state law is proposed, allowing us to close the fluid equations for the electrons without the isothermal hypothesis. A comparison between the fluid model and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…It was also shown using PIC simulations that the average energy (or effective temperature) of the electrons decays in the sheath due to the non-Maxwellian distribution functions mentioned above. Therefore, the usual isothermal sheath theories used to evaluate the sheath potential drop and the secondary emission yield are not correct [24], [25]. A polytropic sheath model has been proposed to overcome the limitation of isothermal models.…”
Section: Plasma Wall Interaction In E×b Discharges Relevant To Plasma...mentioning
confidence: 99%
“…It was also shown using PIC simulations that the average energy (or effective temperature) of the electrons decays in the sheath due to the non-Maxwellian distribution functions mentioned above. Therefore, the usual isothermal sheath theories used to evaluate the sheath potential drop and the secondary emission yield are not correct [24], [25]. A polytropic sheath model has been proposed to overcome the limitation of isothermal models.…”
Section: Plasma Wall Interaction In E×b Discharges Relevant To Plasma...mentioning
confidence: 99%
“…The re-injection of particles however has to be handled carefully. For example, Tavant [29] showed that the use of a virtual axial model with random position re-injection effectively results in large numerical instabilities, which can dramatically impact the simulation results. This drawback has already been observed in 1D-azimuthal simulations [10,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The Particle-in-cell method combined with Monte Carlo type treatment of the collision processes (PIC/MCC) [24][25][26][27][28][29][30][31][32][33][34][35] has been an important approach in the studies of a wide variety of phenomena in CCPs. The discharge models used in PIC/MCC simulations usually adopt several assumptions related to the description of the interaction of plasma species with the boundary surfaces.…”
Section: Introductionmentioning
confidence: 99%